Evaluation of total antioxidant status, total oxidant status and oxidative stress index in some economically important plants from Turkey - Caf, Fatma; Kiliç, Ömer; Algül, Sermin (Progress in Nutrition, 2018)
This study aims to develop antioxidant properties of thirty four economically important plants of Asteraceae and Lamiaceae families, from Turkey. Analyses were done with reliable measurement research kits. Total antioxidant status, total oxidant status were determined with a novel method using available enzyme-linked immuno assay kit (TOS Cat. No: RL0024, TAS Cat. No: RL0017).Total antioxidant (TAS) level of studied Asteraceae and Lamiaceae taxa were detected as 71.61±37.05 mmol/L and 36.97±9.6 mmol/L, respectively. In addition, TAS level of Asteraceae taxa was found to be higher (p